Handbook for Nuclear Weapons Effects under Arctic Conditions. Sanitized. - Keith, J. R.; Wallace, W. E. (1980)
This report describes the changes to be expected in nuclear weapons effects in arctic conditions as compared with the temperature regions of the works. Previous research in this area has been reviewed and relevant information is presented. The emphasis was placed on low altitude and underwater bursts and effects. Inadequacies and uncertainties in current prediction techniques are given. The characteristics of the arctic region of importance in nuclear effect calculations are given. The effects considered include air blast, cratering, thermal radiation, nuclear radiation, EMP, HF communication degradation, water shock, water waves and acoustic effects. Prepared in cooperation with Underwater Systems, Inc., Rockwell, MD.